“Male-supported, female-initiated” - Eliza Govender; Yonela Vukapi; Phiwe Nota (Communicare)
HIV and AIDS remain one of the leading public health challenges in the world, with young women in sub-Saharan Africa bearing the brunt of HIV infection. Female vulnerability to HIV infection is exacerbated by socio-cultural, economic and biological dynamics. Vaginal microbicide, one of the first topical pre-exposure prophylaxis (PrEP) innovations for HIV prevention can offer new hope for women, but an understanding of the local cultural context and its influence on product acceptability is fundamental for effective HIV communication strategies. Critical health communication navigates through the complexities of cultural discourses to create awareness among women in dominant cultural settings. As a means of understanding the key determinants for effective HIV communication, this paper used thematic analysis of data from a study among female students at the University of KwaZulu-Natal regarding their preferences and the acceptability of two microbicide technologies: the tenofovir gel and the dapivirine ring. Key findings indicate that microbicides give women more options for self-protection and cater for diverse sexual encounters, and that their covert use empowers women to use the products even if male partners do not support this. However, women felt more empowered with “male-supported, female-initiated” HIV prevention options. The study suggests that in providing HIV prevention options to women, culturally appropriate messages must be considered. We suggested that topical PrEP must be communicated as a “male-supported, female-initiated” HIV prevention option in rural KwaZulu-Natal contexts.